Behaviour of bean cultivars in sole and associated cropping with corn in Espírito Santo state, Brazil - Neto, João Francisco Candal; Pacova, Braz Eduardo Vieira; Guidoni, Antonio Lourenço (Pesquisa Agropecuaria Brasileira, 2014)
In order to select bean (Phaseolus vulgaris L.) cultivars adaptable as to associated cropping and to solo cropping, and to verify if there is any correlation between the yield of both cultivation systems, seven experiments were carried out at Afonso Cláudio and Domingos Martins, ES, Brazil, from 1978 to 1980. The most productive cultivars in both systems were Rio Tibagi and Ricopardo 896: 1,293 and 1,208 kg/ha, in associated cropping, and 1,683 and 1,725 kg/ha in sole cropping, respectively. There has been a positive and significative correlation (r = 0.74* *) between sole and associated cropping yield. The associated cropping presented an average decrease of 37.7%, in relation to solo cropping. The development of diseases was lower in the associated cropping.